INTERNET SERVICE PROVIDER SEBAGAI TREND BISNIS DALAM ERA TEKNOLOGI INFORMASI DI INDONESIA - Frans Warmanto (Center for Economic Studies Universitas Katolik Parahyangan, 2001)
Internet Service Provider (ISP) or known as Portal has become business trend In the rapid growing of information technology revolution in marketing, Communication, or in economic as a whole, The tight competition inside has Lead the player to manage their portal carefully so they can have the power to Compete each other. The consumer need and want of the excellent service Offered is the most reason to develop ISP in spite of catching the market share. So the power of survive will depend on their implemented strategies. Being Creative and innovative continuously become the key words to success